Habituals in contrast: Danish 'pleje' and its Dutch and German translations (Linguistics in Amsterdam, 2021)
This paper investigates the expression of habitual meaning in the three Germanic languages Danish, Dutch, and German. We first survey habitual expressions in Danish, arguing that the primary means for expressing habitual meaning is the catenative verb pleje ‘usually do, used to’. Using a parallel corpus of Danish lit-erary texts from two time periods (1843–1901 and 1973–1987) and their transla-tions into Dutch and German, we then investigate how pleje is translated into these two languages. Although closely related verbs are available in Dutch (ple-gen) and German (pflegen), our findings suggest that there is no single way of conveying habituality in these two languages. Instead, habituality can be ex-pressed by a number of different strategies which are subject to diachronic and stylistic variation. In addition, the material shows that Danish pleje may have a contrastive function along with its habitual meaning, expressing an explicit con-trast between the usual and the current state of affairs.